The relationship between restaurant atmospheric and customer satisfaction: Malaysian restaurants contexts / Nurul Fathiah Sufiah Mohd Najhan ... [et al.] - Mohd Najhan, Nurul Fathiah Sufiah; Mohd Shahril, Aslinda; Tamby chik, Chemah; Chang, Flora (Universiti Teknologi MARA (UiTM), 2022)
Although the literature has established a selection of atmospheric combinations such as restaurant elements, layout, ambience, and space design, restaurant atmospherics studies remain scarce in Malaysia. Limited studies were found to examine the overall relationship of restaurant atmospherics and employee factor as a moderating effect on customer satisfaction. This study examined the restaurant atmospherics attributes and the moderating effect of employee factor on customer satisfaction. This study used the quantitative method and, questionnaires were distributed to 320 respondents dining in the restaurants in the Bukit Bintang area, Kuala Lumpur. The results were then analysed using SPSS and, it was found that the employee factor does not moderate the relationship between restaurant atmospherics and customer satisfaction. However, the study found that physical environment, ambience, and spatial layouts significantly impact customer satisfaction. Next, the limitation, recommendation, and implications of the study were suggested for future research.